Providing visual directives via a smart watch to a student with Autism Spectrum Disorder: an intervention note. (1st October 2020) - O'Brien, Amanda M.; Schlosser, Ralf W.; Shane, Howard; Wendt, Oliver; Yu, Christina; Allen, Anna A.; Cullen, Jacqueline; Benz, Andrea; O'Neill, Lindsay
Abstract: Smart watches are discreet and wearable tools that may be repurposed to improve directive-following for individuals with autism spectrum disorder (ASD). Specifically, a mentor can transmit just-in-time (JIT) visual supports (e.g., video clips, photographs, text) that depict an upcoming directive to a learner's smart watch to prompt the learner as needed from a distance. Using a single-case multiple probe design across settings, this investigation evaluated the effectiveness of providing text-based prompts on an Apple Watch 1 to a child with ASD within a school setting. A mentor transmitted 2-step written directives via text message to the participant's Apple Watch. The participant was instructed to attend to, read, and follow directives received on the watch. Results demonstrated that the intervention improved directive-following as well as increased the instructor's distance from the learner. It is proposed that JIT supports sent to a learner's smart watch may reduce the obtrusiveness of traditional prompting while also maintaining the naturalness of ongoing social or academic interactions. Clinical limitations and implications are discussed.